2016
DOI: 10.1002/2015jd023749
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian transport simulations of volcanic sulfur dioxide emissions: Impact of meteorological data products

Abstract: Sulfur dioxide (SO2) emissions from strong volcanic eruptions are an important natural cause for climate variations. We applied our new Lagrangian transport model Massive‐Parallel Trajectory Calculations to perform simulations for three case studies of volcanic eruption events. The case studies cover the eruptions of Grímsvötn, Iceland, Puyehue‐Cordón Caulle, Chile, and Nabro, Eritrea, in May and June 2011. We used SO2 observations of the Atmospheric Infrared Sounder (AIRS/Aqua) and a backward trajectory appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 100 publications
(176 reference statements)
0
66
0
Order By: Relevance
“…More details on the SI can be found in Hoffmann et al (2014Hoffmann et al ( , 2016 and Heng et al (2016). AIRS was able to detect the SO 2 cloud from the beginning of the eruption of Sarychev on 12 June 2009 up to 5 weeks later.…”
Section: Airsmentioning
confidence: 96%
See 1 more Smart Citation
“…More details on the SI can be found in Hoffmann et al (2014Hoffmann et al ( , 2016 and Heng et al (2016). AIRS was able to detect the SO 2 cloud from the beginning of the eruption of Sarychev on 12 June 2009 up to 5 weeks later.…”
Section: Airsmentioning
confidence: 96%
“…The Massive-Parallel Trajectory Calculations (MPTRAC) model is a Lagrangian particle dispersion model, which is particularly suited to study volcanic eruption events Hoffmann et al, 2016). In the MPTRAC model, trajectories for individual air parcels are calculated based on numerical integration of the kinematic equation of motion and simulations are driven by wind fields from global meteorological reanalyses.…”
Section: Mptracmentioning
confidence: 99%
“…The calculations were performed with the Lagrangian particle dispersion model introduced by Hoffmann et al (2016b) using both the ERA-Interim and the ECMWF operational analysis as meteorological input data. The calculations cover a time period of 24 h. We conducted the calculations for ensembles of 100 trajectories to take into account the broad measurement volume of MIPAS as well as atmospheric diffusion and subgrid-scale wind fluctuations.…”
Section: Datementioning
confidence: 99%
“…The 12-hourly analyses were combined with short-term forecasts in between to obtain data with a 3-hourly time step. Hoffmann et al (2016) showed that ECMWF operational analyses and forecasts outperform current reanalysis data products in terms of transport deviations for simulations of volcanic sulfur dioxide emissions in the upper troposphere and stratosphere. Hoffmann et al (2017) showed the same for the trajectory calculations for superpressure balloon observations in the Antarctic lower stratosphere.…”
Section: Ecmwf Operational Analysismentioning
confidence: 99%
“…MPTRAC has been developed to support the analysis of atmospheric transport processes in the free troposphere and stratosphere. In recent studies, it has been used to perform transport simulations for volcanic eruptions and to reconstruct time-and height-resolved emission rates for these events Hoffmann et al, 2016;Wu et al, 2017). An intercomparison of meteorological analyses and MPTRAC trajectory calculations with superpressure balloon observations in the Antarctic lower stratosphere was presented by Hoffmann et al (2017).…”
Section: Lagrangian Particle Dispersion Modelmentioning
confidence: 99%